2009
DOI: 10.1016/j.lwt.2009.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk supplementation with skim milk powder, whey protein concentrate and sodium caseinate on acidification kinetics, rheological properties and structure of nonfat stirred yogurt

Abstract: a b s t r a c tMilk supplementation with milk proteins in four different levels was used to investigate the effect on acidification and textural properties of yogurt. Commercial skim milk powder was diluted in distilled water, and the supplements were added to give different enriched-milk bases; these were heat treated at 90 C for 5 min. These mixtures were incubated with the bacterial cultures for fermentation in a water bath, at 42 C, until pH 4.50 was reached. Chemical changes during fermentation were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
123
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 31 publications
15
123
0
11
Order By: Relevance
“…The data showed that the yoghurt prepared with the HRP and FA-treated milk had the largest hysteresis loop area while that prepared with the control milk had the smallest one (Table 3). It is known that the hysteresis loops is assumed to be the difference between the energies required for structural breakdown and rebuilding, and stronger thixotropy led to greater hysteresis loops (Damin et al 2009). In the present work, the yoghurt prepared with the HRP and FA-treated milk showed the largest thixotropy while that prepared with the control milk exhibited the smallest thixotropy.…”
Section: Resultsmentioning
confidence: 99%
“…The data showed that the yoghurt prepared with the HRP and FA-treated milk had the largest hysteresis loop area while that prepared with the control milk had the smallest one (Table 3). It is known that the hysteresis loops is assumed to be the difference between the energies required for structural breakdown and rebuilding, and stronger thixotropy led to greater hysteresis loops (Damin et al 2009). In the present work, the yoghurt prepared with the HRP and FA-treated milk showed the largest thixotropy while that prepared with the control milk exhibited the smallest thixotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Akalin et al (2012) studied textural characteristics of probiotic yogurts fortified with sodium calcium caseinate (SCaCN) and WPC; and reported that fortification with SCaCN increased the firmness more than WPC in probiotic yogurts during storage (P < 0.05). Damin et al (2009) also showed that yogurt made with milk supplemented with sodium caseinate resulted in significant increase in firmness. However, Jelen et al (1987) observed no significant difference in firmness of yoghurt gels made from milk with various casein to whey protein ratios.…”
Section: Effect Of Mfop Fortification and Storage Time On Texture Promentioning
confidence: 91%
“…The control yoghurt and yoghurt sample IX were considered to be the least and most stable, respectively, as the respective hysteresis loop areas of the control yoghurt, yoghurt samples III, and IX were 126.5, 201.6, and 267.5 (Table 2). Hysteresis loop is assigned to be the difference between the energies required for structural breakdown and rebuilding (Damin et al, 2009). Larger hysteresis loop areas of the yoghurt samples III and IX reflected that greater energy was required for their structural breakdown.…”
Section: Samplesmentioning
confidence: 99%
“…WPC and WPI both can be used in yoghurt production in order to enrich protein content. Whey protein addition has been observed to increase strength of yoghurt gels (Krzeminski, Grosshable, & Hinrichs, 2011;Lucey, Munro, & Singh, 1999), decrease syneresis (Kücükcetin, 2008), and enhance viscosity (Damin, Alcântara, Nunes, & Oliveira, 2009). It is known that thermal treatment of whey protein induces protein denaturation and more importantly polymerization of whey protein (Fitzsimons, Mulvihill, & Morris, 2008), which brings about modified properties to whey protein.…”
Section: Introductionmentioning
confidence: 99%